Variable designs of vertical axis wind turbines—a review - Lee, Ken-Yeen; Cruden, Andrew; Ng, Jo-Han; Wong, Kok-Hoe (Frontiers in Energy Research, 2024)
Omnidirectionality and simple design make VAWTs more attractive compared to HAWTs in highly turbulent and harsh operational environments including low wind speed conditions where this technology shines more. However, the performance of VAWTs is lacking compared to HAWTs due to low turbine efficiency at downstream caused by large wake vortices generated by advancing blades in the upstream position. Introducing variable design methods on VAWT provides better adaptability to the various oncoming wind conditions. This paper presents state-of-the-art variable methods for performance enhancement of VAWTs to provide better direction for the wind industry. The variable VAWT design can increase the lift and torque, especially at the downstream regions by managing the blade-to-wake interaction and blade angle of attack (AoA) well, hence contributing to the performance enhancement of VAWTs. In addition, the self-starting capabilities have also been found to improve by employing variable methods with a better angle of attack on the turbine blades. Nevertheless, the complexity of varying mechanisms and structural rigidity are the main challenges in adopting this idea. Yet, it possesses great potential to develop higher-efficiency VAWT systems that can operate in a wide range of wind speeds.